2017
DOI: 10.1111/jgs.14912
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Current Diagnostic Criteria for Acute Bacterial Infection in Older Adults in the Emergency Department

Abstract: Objectives To evaluate the accuracy of emergency department (ED) physicians’, the Loeb criteria, and CDC guideline diagnoses of acute bacterial infection in older adults compared to a gold standard expert review. Design Prospective, observational study. Setting Urban, tertiary-care ED. Participants ED patients aged ≥65 years, excluding those incarcerated, traumas, non-English speaking, or unable to consent. Measurements Two physician experts identified bacterial infections using clinical judgement, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…The primary study included 424 subjects . Table provides patient characteristics overall and stratified by presence of infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary study included 424 subjects . Table provides patient characteristics overall and stratified by presence of infection.…”
Section: Resultsmentioning
confidence: 99%
“…1 Accurate infection diagnosis is complicated by the absence of typical symptoms found in younger adults, lack of accurate diagnostic criteria, absence of timely culture results, long-term microorganism colonization, and comorbidities. [2][3][4][5] Both overdiagnosis and underdiagnosis can occur. 2,6 Overdiagnosis may result in increased costs, inappropriate antibiotic use, missed alternative diagnoses, and preventable admissions.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both under‐diagnosis and over‐diagnosis is common, but over‐diagnosis seems the more pressing problem in geriatric emergency medicine and is the focus of this article. A retrospective study of emergency admissions of those aged 75+ years treated with intravenous antibiotics for a UTI found that 43% did not meet defined criteria for that diagnosis.…”
Section: Uti In Older Personsmentioning
confidence: 99%
“…al.’s interest in our article and thank them for their comments. 1,2 They are correct in noting that the 24/7/365 nature of emergency medicine can pose challenges to interpretation of clinical research. The ideal population they describe is not obtainable in the vast majority of emergency departments (EDs) due to staffing challenges and expense associated with around the clock research coordinator coverage.…”
Section: To the Editormentioning
confidence: 99%